Sosialisasi Program Pendampingan Kelompok Tani Desa Sidomulyo Di Mojokerto Jawa Timur - Achmad Rijanto; Suesthi Rahayuningsih (CV. Multi Kreasi Media, 2025)
This community service activity was carried out in Seno hamlet, Sidomulyo village, Mojokerto district, East Java province. This activity is in partnership with the Margo Rukun farmer group. The purpose of this community service activity is to provide information to members of the farmer group about several mentoring program activities carried out for the Margo Rukun farmer group in Sidomulyo village in the fields of production and marketing. The method of this activity is a community education method in the form of socialization in the form of direct face-to-face meetings between the community service implementation team and members of the farmer group. This socialization is the delivery of mentoring programs in the fields of production and marketing. Mentoring in the field of production is mentoring in the use of hand tractors to cultivate agricultural land and the use of electric pest sprayers. While mentoring in the field of marketing is the use of digital marketing for marketing agricultural products. The results achieved in this community service activity are that members of the farmer group know and understand the various mentoring activity programs that will be applied to the farmer group. The farmer group strongly supports the mentoring activities in the use of hand tractors to cultivate agricultural land, mentoring in the use of electric pest sprayers and mentoring in the use of digital marketing for marketing agricultural products.